Reflection of positive colors and negative colors in Pak Kaduk's narrative: A pragmatic analysis - Daud, Muhammad Zaid; Subet, Mary Fatimah; Awang Pawi, Awang Azman (UPSI Press, 2024)
Pak Kaduk (PK) is a prominent character in folk literature, particularly humorous stories, characterized by their comedic elements. These narratives frequently possess a profound impact on audiences, as they draw upon the experiences of traditional Malay communities. The primary intent behind crafting such humorous tales lies in providing entertainment, critiquing societal norms, and imparting moral lessons to readers. Thus, this study endeavours to dissect Pak Kaduk's narrative style, focusing specifically on his use of colour and emotion. This qualitative investigation employs document analysis as its primary methodology, based on the reputable framework of Relevance Theory (Sperber & Wilson, 1986; 1995). The research data was obtained from two significant works, namely 'Lukisan Zaman' by Shari (1991) and 'Collection of 336 Malaysian Folktales' by Puteh and Said (2008). The findings reveal that the author uses cape flowers and colours as symbols of diversity, which encapsulates Pak Kaduks myriad emotions. The plethora of colours available in cape flowers serves to emphasize the notion of diversity, with each hue representing distinct emotional states. Notably, white, and yellow signify positivity, while red and black connote negativity. This study not only sheds light on Pak Kaduks storytelling techniques, but also provides insights into the societal critiques embedded within these narratives. It also shows how important it is to acknowledge and interpret the nuanced relationship between colour and emotion in folk literature.